YouTube™ as a source of information on oral habits - Huseyin Simsek; Suleyman Kutalmýþ Buyuk; Ebru Çetinkaya (Wolters Kluwer Medknow Publications, 2020)
Background: The aim of this study was to evaluate the content of oral habit videos on YouTube™. Materials and Methods: The four keywords "Oral Habits," "Thumb Sucking," "Tongue Thrust", and "Finger Sucking" relevant terms oral habits were searched on YouTube™. The videos sorted by view count were screened and evaluated. The following exclusion criteria were defined as; non-English videos, unrelated to a topic, poor audio-video quality, and duplication. A hundred videos were analyzed for general video characteristics (number of views, likes, dislikes, number of comments, and uploaded date) the purpose of the video, information content, audio-visual quality, and viewers' interaction index. Results: The top hundred videos have been viewed an average of 26,870.83 times. Most videos were uploaded by dentists (n = 29; 29.0%). Most of the videos (44.0%) were classified as having moderate general information content and 38.0% were rated as good, and 18.0% were rated as poor. Videos generally involved information about oral habits (82.0%), followed by personal experience (12.0%). The viewers' interaction index of all evaluated YouTube™ videos was 0.59. Good content videos had a significantly higher interaction index than the other groups (P = 0.011). Conclusions: YouTube™ videos about the oral habits are generally inadequate and patients must be recommended to view them with caution. High quality and more informative videos about oral habits in dentistry should be uploaded to YouTube™ by professionals.